2003
DOI: 10.1046/j.1365-313x.2003.01764.x
|View full text |Cite
|
Sign up to set email alerts
|

Sodium transport and HKT transporters: the rice model

Abstract: SummaryNa uptake in the roots of K -starved seedlings of barley, rice, and wheat was found to exhibit fast rate, low OsHKT genes were fairly constant and insensitive to changes in the K and Na concentrations of the nutrient solution. In roots, the expressions were much lower than in shoots, except for OsHKT4 and OsHKT1 in K -starved plants. We propose that OsHKT transporters are involved in Na movements in rice, and that OsHKT1 speci®cally mediates Na uptake in rice roots when the plants are K de®cient. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
365
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(386 citation statements)
references
References 58 publications
(107 reference statements)
15
365
0
3
Order By: Relevance
“…Moreover, the tail currents of AtHKT1;1 also showed a time-independent leak profile (Fig.1B). To sum up, the results indicated that OsHKT2;4 produces a unique current profile that is absent in oocytes expressing other HKT members, including several previously described for rice (5,6,(12)(13)(14). Channel.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…Moreover, the tail currents of AtHKT1;1 also showed a time-independent leak profile (Fig.1B). To sum up, the results indicated that OsHKT2;4 produces a unique current profile that is absent in oocytes expressing other HKT members, including several previously described for rice (5,6,(12)(13)(14). Channel.…”
Section: Resultssupporting
confidence: 51%
“…Compared with a single AtHKT1;1 gene in the dicot model, Arabidopsis, rice, a monocot model, contains nine HKT-like genes (12), a striking departure from Arabidopsis. Available data suggest that various members within the rice HKT family may belong to either group 1 or to group 2 HKTs (13,14).…”
mentioning
confidence: 99%
“…Cereals possess a much larger number of HKT genes, e.g. five to 11 genes in the different wheat genomes (Huang et al, 2008) and nine genes in rice (Oryza sativa; Garciadeblás et al, 2003), leading to functional diversity within this family (Jabnoune et al, 2009;Corratgé-Faillie et al, 2010). Based on functional studies in heterologous systems (Xenopus oocytes or yeast cells) and phylogenetic analyses, higher plant HKT transporters have been sorted out into two subfamilies .…”
mentioning
confidence: 99%
“…High-affinity Na + uptake has been reported in K + -starved seedlings of wheat [93], rice [44], and barley [53]. However, there is no direct evidence that a channel/ transporter functions in Na + -selective uptake in plant roots.…”
Section: Sodium Transportersmentioning
confidence: 99%
“…Unlike Arabidopsis containing one HKT gene, seven HKT genes have been identified in rice cv. Nipponbare [44]. Given this large number of genes, rice may be a better model for understanding the role of HKTs in regulating Na + transport [142].…”
Section: Sodium Transportersmentioning
confidence: 99%